Association Between GABRG2 and Self-Rating of the Effects of Alcohol in a French Young Adult Sample - Moe JS; Bramness JG; Bolstad I; Mørland JG; Gorwood P; Ramoz N (Risk Management and Healthcare Policy, 2025)
Jenny Skumsnes Moe,1,2 Jørgen G Bramness,1– 4 Ingeborg Bolstad,1,5 Jørg Gustav Mørland,3,6 Philip Gorwood,7,8 Nicolas Ramoz7,8 1Research Center for Substance Use Disorders and Mental Illness, Innlandet Hospital Trust, Brumunddal, Norway; 2Institute for Clinical Medicine, The Arctic University of Norway, Tromsø, Norway; 3Department of Alcohol, Tobacco, and Drugs, Norwegian Institute of Public Health, Oslo, Norway; 4Section for Clinical Addiction Research, Oslo University Hospital, Oslo, Norway; 5Department of Health and Social Science, Inland Norway University of Applied Sciences, Elverum, Norway; 6Institute of Clinical Medicine, University of Oslo, Oslo, Norway; 7Université Paris Cité, Inserm U1266, Institut de Psychiatrie et Neurosciences de Paris (IPNP), Team Vulnerability of Psychiatric and Addictive Disorders, Paris, France; 8GHU PARIS Psychiatrie & Neurosciences, Hôpital Sainte-Anne, CMME, Paris, FranceCorrespondence: Jenny Skumsnes Moe, Research Center for Substance Use Disorders and Mental Illness, Innlandet Hospital Trust, P.O. Box 104, Brumunddal, 2381, Norway, Email jenny.s.moe@uit.noPurpose: Alcohol use is a leading risk factor for preventable death, injury, and disease globally. Low sensitivity to the effects of alcohol is influenced by genes and predicts risk for harmful alcohol use and alcohol use disorder (AUD). Alcohol induces effects partly by modulation of gamma-aminobutyric acid receptors type A (GABAARs). This study investigates the relationship between genetic variation in GABAAR subunit genes and individual alcohol sensitivity among French university students.Patients and Methods: The study involved 1,409 French university students (34.5% women; mean age 20.3 years). Alcohol sensitivity was measured by the Self-Rating of the Effects of Alcohol Scale (SRE). SRE-scores from initial drinking, regular drinking, and heavy drinking were investigated for correlations with alcohol consumption and for associations with single nucleotide polymorphisms (SNPs) in GABAAR subunit genes (GABRA2, GABRG2, GABRA6).Results: We replicated correlations between low alcohol sensitivity and high alcohol consumption. We further found an association between the minor allele in rs211014 (GABRG2) and higher SRE-scores, linked to dizziness and motor incoordination. Genetic variation in GABRG2 has previously been associated with processes involving motor coordination (alcohol withdrawal, febrile- and epileptic seizures).Conclusion: The results from our study suggest that genetic variation in GABRG2 may influence alcohol sensitivity, which could inform strategies for assessing risk for harmful alcohol use and AUD.Keywords: alcohol use, GABRG2, self-rating of the effects of alcohol, genetic, AUD, AUDIT